Changes in friluftsliv (outdoor recreation) activities among Norwegian adolescents during the SARS-CoV-2 pandemic - Sæther, Eivind; Mikalsen, Stian; Lagestad, Pål (Frontiers in Sports and Active Living, 2023)
Friluftsliv (outdoor recreation) activities can provide both physical activity and experiences in nature and improve quality of life. Regular physical activity is critical for young people's physical, social, and mental health. During the SARS-CoV-2 pandemic in 2020-2022, schools, gyms, and swimming pools were closed, and athletic teams and other physical activity services were prohibited from holding events. Despite these restrictions, access to nature and most friluftsliv persisted throughout the pandemic. The purpose of this study is to elucidate how the degree of activity in various friluftsliv activities changed during the pandemic, as well as identify the significance that friluftsliv had for the experience of community prior to and during the pandemic. To achieve this goal, 287 young people aged 16-19 answered a questionnaire. The results showed that self-reported total friluftsliv decreased significantly by 12.1% during the pandemic compared to self-reported total friluftsliv activity in the year before the pandemic occurred. Modern friluftsliv experienced an overall activity decline in participation of 24.8%. Two of these activities had a significant decrease in activity level, while three of the activities had an unchanged level of activity. Traditional friluftsliv also experienced a significant decrease of 7.8%, with six of the seven friluftsliv activities exhibiting a significant decrease in activity level during the pandemic. Regarding the importance of friluftsliv for the experience of community, a substantial number of participants felt that friluftsliv activities had been more important during the pandemic than prior to the pandemic. In addition, many respondents indicated that the desire to be with friends, family, and girlfriends/boyfriends had become more important during the pandemic than before it. The findings related to the importance of friluftsliv activities to experiencing community were not unexpected. However, it was somewhat unanticipated that the two-year pandemic did not lead to more friluftsliv among young people, given the unavailability of other avenues of physical activity - which is concerning from a public health perspective, in terms of social, psychological, and physical health.